Projected linear response theory for charge-exchange excitations and double beta decay - Krmpotic, Francisco (1993)
The projected random phase approximation (PRPA) for charge-exchange excitations is derived from the time-dependent variational principle. Explicit results for the unperturbed energies (including the self-energy corrections), the PRPA matrices, and the transition matrix elements are presented. The effect of the projection procedure on the two-neutrino ββ decay in 76Ge is briefly discussed.